Data mobilisation for historical records of vascular plants in eastern Asia: V. L. Komarov’s expedition to Far-Eastern Russia, China and Korea from 1895 to 1897 - Chin Sung Chang; Kae Sun Chang; Hui Kim (Biodiversity Data Journal)
Historical collections of herbaria and literature play a crucial role in documenting biodiversity information. The botanical biodiversity of northern Asia is significantly understudied compared to other regions of China and Japan. In particular, the biodiversity patterns in China's three north-eastern provinces, North Korea and the Russian Far East remain poorly understood, with substantial gaps when compared to the records of species distributions in Japan, South Korea and inland China. The Komarov data, orginally written in Russian, required extensive efforts to georeference the 130-year-old Chinese and North Korean place names to their modern equivalents and translate historical names to their current forms. This study aims to restore the Komarov data, including both specimen records and occurrence data, to assist the broader scientific and environmental community in recovering key biodiversity data from the past of northeast Asia. The impetus for this work was the need to assign geographic coordinates to plant specimens collected in the region and to V.L. Komarov's observations as primary occurrence data from 1895 to 1897.In this study, we present historical occurrence data obtained from the north-eastern Asian plant expedition carried out from 1895 to 1897 by V.L. Komarov in Far-Eastern Russia, Heilongjiang, Jilin, the eastern region of Liaoning in China and the northern region of Korea. The occurrences were georeferenced to more than 350 sites in Russia, China and Korea. All occurrences were georeferenced and species names were cross-checked and taxonomically updated using our own Asian plant checklist. The dataset consists of 21,114 primary occurrence records, comprising 6,956 specimens and 14,158 observation records. The outcome clearly shows that such initiatives can reveal an unexpected amount of highly valuable biodiversity information for “data-poor” regions.